Imaging Monitoring Technology of Fractures Around Horizontal Wells with Multi-Stage Fracturing in Water Injection Development - ZHENG Gang; ZHU Hongzheng; LI Dajian; WANG Xu; TANG Xiangdong; SU Zubo (Cejing jishu)
Horizontal wells are widely used in low permeability oil and gas fields as an important technology to realize beneficial development. However, with the extension of production time, due to the influence of well structure and waterflood development mode, the production capacity loss of horizontal wells caused by water flooding is prominent, which seriously affects the economic benefit development of oil fields. In China, there is a lack of mature and reliable methods to test the production status of horizontal wells, making it difficult to accurately identify the main causes and conditions of water production in these wells. To address this issue, an imaging monitoring technology for fractures around wells has been proposed. This technology employs a crawler to deploy a 3D far-field sonic imaging logging tool, allowing for the detection and recognition of fracture development around multi-stage fractured horizontal wells under waterflooding conditions. This technology enables the qualitative identification of the primary water-producing locations, water inflow directions, and causes of water production in horizontal wells, thereby facilitating rapid and accurate water shutoff and effectively restoring well productivity. The application of the perimeter fracture imaging monitoring technology at G Ping well 1 of Changqing oilfield indicates that, the technology detected the clear communication of the 5th and 6th sections of the fractured zone near the wellbore in the pressure-fracturing section, as well as the very well-developed fractures in the far field, which are the dominant channels for water inflow, and the results are consistent with the fluid scanning imaging petrophysical test interpretation results, verifying the adaptability of the technology. The imaging monitoring technology of the fractures around the well realizes the accurate identification of the water interval and the main interval of the remaining oil exploitation and has solved the problems of unclear out-of-pipe and in-layer flow, as well as the difficulty of identifying the direction for subsequent water blocking and oil recovery.